PENINGKATAN HASIL DAN AKTIVITAS BELAJAR MATA PELAJARAN AKUNTANSI DENGAN METODE RESITASI PRA-PEMBELAJARAN - Santoso, Djoko (Dinamika Pendidikan, 2013)
The background of this research was the study result of Accounting subject was unsatisfactory, thus it was needed an appropriate learning strategy. The objective of the research was to improve Accounting’s study result and learning activities through Pre-learning Recitation method. The subjects of the research were XI grade students of IPS 2. It was a class action research with two cycles. Each cycle consisted of four stages; planning, implementation, observation and reflection. The data were collected by tests and analyzed by comparative descriptive and reflection. The result of the study showed that the pre-learning Recitation could improve students’ activities and achievement in both; score and completeness. Based on the first condition of pre-cycle with the KKM (minimum score) 75, it was 51.73% of 29 students for the completeness and the mean was 74.70.  After implementing the method, it was 78.57% of 28 students who completed and the mean was 83.23 in the 1st cycle. Then, it was 92.86% for the completeness and the mean was 89.23 in the 2nd cycle.